2014
DOI: 10.21149/spm.v56i5.7380
|View full text |Cite
|
Sign up to set email alerts
|

Dieta y cáncer gástrico en México y en el mundo

Abstract: El cáncer gástrico (CG) es la cuarta causa de muerte por cáncer a nivel global. La dieta y el consumo de alcohol y tabaco, además de la infección por Helicobacter pylori determinan un gran número de casos de esta neoplasia. Algunos alimentos contienen sustancias que podrían influir en el proceso de carcinogénesis gástrica, aunque los mecanismos subyacentes no están completamente dilucidados. En México y el mundo, la disminución en el consumo de frutas, vegetales no feculentos y allium, leguminosas y alimentos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(34 reference statements)
0
1
0
4
Order By: Relevance
“…A few experimental studies showed that capsaicin could suppress the growth of GC cells or inhibit metastatic activity [ 47 , 48 ]. However, many epidemiological studies have identified that a high capsaicin diet is positively correlated with an increased risk of GC [ 7 , 12 14 ]. Additionally, capsaicin is commonly employed to induce GC in combination with Helicobacter pylori [ 8 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few experimental studies showed that capsaicin could suppress the growth of GC cells or inhibit metastatic activity [ 47 , 48 ]. However, many epidemiological studies have identified that a high capsaicin diet is positively correlated with an increased risk of GC [ 7 , 12 14 ]. Additionally, capsaicin is commonly employed to induce GC in combination with Helicobacter pylori [ 8 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Em relação ao sal, embora quantidades suficientes de sal sejam necessárias, o consumo excessivo pode atuar como um estimulante da mucosa gástrica, levando à gastrite atrófica, aumento da síntese de ácido desoxirribonucleico (DNA) e proliferação celular, fornecendo assim a base para a incidência de cancro gástrico. Como fatores protetores da doença encontram-se documentados as frutas, as verduras, o caroteno e a vitamina C (American Cancer Society, 2017; Hernández-Ramírez & López-Carrillo, 2014;Lever-Rosas et al, 2014;Smyth et al, 2020;Song et al, 2015;Yusefi et al, 2018).…”
Section: íNdíce De Figurasunclassified
“…Assim, a evidência científica disponível permite definir um perfil de risco dietético para o desenvolvimento de cancro gástrico nomeadamente: baixo risco, quando se verifica consumo de frutas, hortaliças, vegetais, leguminosas e alimentos ricos em selénio (farinha de trigo, gema de ovo, entre outros) com ação antioxidante, aumentando a resistência do sistema imunológico; e, alto risco, quando estamos perante consumo de sal, alimentos salgados, carnes processadas, alimentos fumados e alimentos de origem animal assados (Hernández-Ramírez & López-Carrillo, 2014).…”
Section: íNdíce De Figurasunclassified
See 2 more Smart Citations